IMAGE ANALYSIS OF PEARLITE SPHEROIDIZATION BASED ON THE MORPHOLOGICAL CHARACTERIZATION OF CEMENTITE PARTICLES - Nutal, Nicolas; Gommes, Cedric J; Blacher, Silvia; Pouteau, Philippe; Pirard, Jean-Paul; Boschini, Frédéric; Traina, Karl; Cloots, Rudi (Image Analysis and Stereology, 2011)
Pearlite spheroidization is a metallurgical process in steels by which cementite lamellae decompose into spheroids, a process accompanied by a decrease of the Vickers hardness of the samples. In this study, different methods are compared for measuring cementite particles length and width from scanning electron micrographs. Based on a test-image, a so-called ribbon-like method is proposed for measuring particles length and width, and for discriminating lamellae from spheroids. Differently heat-treated samples are prepared and characterized. The results of analysis are used to rationalize the evolution of the microstructure of the samples. Compared to the classical DeHoff shape factor, it is shown that new insight into the spheroidization process is gained by analyzing the lamellar length and width distributions.